Traumatology of the facial skull in childhood - Freudlsperger, Christian; Hoffmann, Jürgen; Ristow, Oliver (Laryngo-Rhino-Otologie, 2020)
Associated injuries are a common feature in pediatric facial fractures, which reinforce the importance of a complete initial assessment of a child with facial trauma. Particular kinds of fracture tend to occur at specific anatomic sites in children, with the severity and extent of the fracture varying according to the patient's age and the stage of skeletal development. The frequency of severe fractures increases with age, as does the frequency of surgically treated fractures. Maxillofacial surgical intervention is indicated only for the repair of severely displaced fractures that are likely to cause functional impairment, esthetic deformity, or both. The effect of treatment on long-term growth and development must be the cornerstone when choosing the optimal therapeutic option. While internal fixation is routinely used for adult facial trauma patients, the application of these surgical techniques in children is controversial as subperiosteal dissection might disturb the growth of the bone.
Gesehen am 01.04.2020